Transepithelial transport and cytoprotection of novel antioxidant peptides isolated from simulated gastrointestinal digestion of Xuanwei ham. Issue 8 (22nd March 2023) - Hu, Yao-yao; Xiao, Shan; Wang, Bo; Xie, Rui-hong; Cai, Yan-xue; Wang, Ji-hui
Abstract : The antioxidant peptides isolated from Xuanwei ham could be transported by the small intestinal epithelial and have protective effects on H2 O2 -induced damaged HepG2 cells. Abstract : As a traditional fermented meat product, dry-cured Xuanwei ham could be a rich source of bioactive peptides. This study intended to investigate the transepithelial transport and cytoprotection of antioxidant peptides isolated from simulated gastrointestinal digestion of Xuanwei ham. Through ultrafiltration and gel filtration chromatography after simulated digestion, five new antioxidative cell-penetrating peptides (CPPs) with 16–27 amino acid residues were identified, and protective effects of the pretreatment with GHYTEGAELVDSVLDVVRK (GK-19) and TDEFQLHTNVNDGTEFGGSIYQK (TK-23) on H2 O2 -induced damaged HepG2 cells were investigated. The results showed that the peptide TK-23 at 0.5 mg mL −1 showed a good antioxidant activity through upregulating the activity of antioxidant enzymes (CAT, SOD and GR) and decreasing the MDA level in H2 O2 -induced damaged HepG2 cells with a better protective effect compared to GSH. Our observations of novel antioxidant CPPs with 16–27 amino acid residues could enrich the antioxidative CPP database, and these findings could provide data support for further study of CPPs.